Atypical Presentation of Acute Appendicitis: A Case Report - Kloping, Yudhistira Pradnyan; Putri, R. Cita Resti Anantia (The New Ropanasuri Journal of Surgery, 2020)
Despite the fact that acute appendicitis is one of the most common surgical emergencies worldwide, delays in establishing a diagnosis still occur. We report a case of acute appendicitis with an atypical presentation based on the patient’s clinical and laboratory findings. A 25-year-old male was brought with pain in his right lower quadrant. Pain migration, fever, anorexia, nausea, vomiting, or dysuria were denied. Laboratory results were within normal limits. USG examination was not able to visualize the appendix. An abdominal CT-Scan showed a sign of acute appendicitis. The patient was planned for appendectomy. It is important to not immediately rule out the diagnosis of appendicitis because an atypical presentation may be presented and could potentially lead to fatal complications.